Optical coherence tomography findings after drug-coated balloon treatment for de novo coronary artery lesions with eruptive calcified nodule - Matsuda, Kazuki; Lee, Tetsumin; Ashikaga, Takashi; Nozato, Toshihiro; Nagata, Yasutoshi; Kaneko, Masakazu; Miyazaki, Ryoichi; Misawa, Toru; Nagase, Masashi; Horie, Tomoki; Terui, Mao; Kachi, Daigo; et al. (Frontiers in Cardiovascular Medicine, 2025)
The purpose of the present study was to investigate the factors associated with worse clinical outcomes in patients with de novo eruptive calcified nodule (CN) lesions after stent-less percutaneous coronary intervention (PCI) with a drug-coated balloon (DCB), as assessed by optical coherence tomography (OCT) and morphological findings at target lesion revascularization (TLR) or during the follow-up period. We retrospectively enrolled 68 de novo eruptive coronary artery eruptive CN lesions in 58 patients who underwent PCI with DCB. All lesions were treated without stents and underwent both pre- and post-PCI OCT. The patients were divided into two groups: those with or without target lesion failure (TLF), defined as a composite of culprit lesion-related cardiac death, myocardial infarction, and TLR. At a median follow-up period of 650 days, TLF events occurred in 14 lesions (20.6%) and were associated with the absence of medial involvement of coronary artery dissection on post-PCI OCT (28.6% vs. 70.4%, P = 0.006). In the subgroup analysis of 16 lesions with serial OCT imaging (pre-and post-PCI at the index PCI and at TLR or follow-up), TLR occurred in nine lesions. We found CN protrusion at TLR in seven lesions, layered plaque at TLR in one lesion, and suboptimal lumen expansion at the index PCI in another lesion as restenosis patterns. Moreover, CN protrusion was significantly more frequent in TLR lesions than in the seven non-TLR lesions (77.8% vs. 14.3%, P = 0.041). In conclusion, we observed a high incidence of TLF after DCB treatment for de novo eruptive CN coronary artery lesions, which correlated with the absence of medial involvement in dissection. CN protrusion is frequently observed in TLR lesions, whereas late lumen enlargement is predominantly observed in non-TLR lesions.